Impact on weight and glycaemic control in adults with diabetes attending a group- based commercial weight management programme - Avery, Amanda; Nagar, Ravi; Hillier, Sarah; Pallister, Carolyn (Mark Allen Healthcare, 2017)
Healthcare professionals could work in partnership with commercial group weight management programmes (CGWMP) to help people with diabetes lose weight and improve their glycaemic control. The effect of ongoing CGWMP support on diabetes control has not previously been reported. This study evaluates weight loss and glycaemic control in people with diabetes attending a CGWMP. Method: A cross-sectional online survey posted on a CGWMP’s member’s website. The survey asked for reported changes in HbA1c and physical activity and demographics including age, type of diabetes, medications taken and healthcare professional support. The dataset was linked to electronically reported weight and attendances. Data was statistically analyzed to assess percentage of individuals meeting targets for weight reduction and HbA1c and outcome changes with variation between genders, type of diabetes and support. Results: 620 respondents with mean weight loss of 10.0±8.0%; 157 reported a mean reduction in HbA1c of 18±21mmol/mol (1.6±1.9%). 58.2% lost >10% body weight after 24 weeks and 51.5% had achieved HbA1c of <48mmol/l (6.5%). Those with type 2 (n=547) had greater reduction in HbA1c (p=0.034) but not weight (p=0.317) compared to type 1 diabetes (n=73). An increase in physical activity was associated with advise from a healthcare professional (p<0.001) with increases in PA not associated with lower HbA1c (p=0.654). A >5% weight reduction was associated with diabetes medication reduction (p=0.028) and improved glycaemic control (p=0.001). Conclusion: Support provided by the CGWMP resulted in clinically significant weight losses and improvements in HbA1c with reductions in diabetes medication. Attendance at CGWMPs may be an effective long-term strategy and a scalable option to help improve diabetes control.